Temporal and Genotypic Associations of Sporadic Norovirus Gastroenteritis and Reported Norovirus Outbreaks in Middle Tennessee, 2012–2016. (13th November 2019) - Parikh, Meghana P; Vandekar, Simon; Moore, Christina; Thomas, Linda; Britt, Nathan; Piya, Bhinnata; Stewart, Laura S; Batarseh, Einas; Hamdan, Lubna; Cavallo, Steffany J; Swing, Ashley M; Garman, Katie N; et al.
Abstract: Background: In the United States, surveillance of norovirus gastroenteritis is largely restricted to outbreaks, limiting our knowledge of the contribution of sporadic illness to the overall impact on reported outbreaks. Understanding norovirus transmission dynamics is vital for improving preventive measures, including norovirus vaccine development. Methods: We analyzed seasonal patterns and genotypic distribution between sporadic pediatric norovirus cases and reported norovirus outbreaks in middle Tennessee. Sporadic cases were ascertained via the New Vaccine Surveillance Network in a single county, while reported norovirus outbreaks from 7 middle Tennessee counties were included in the study. We investigated the predictive value of sporadic cases on outbreaks using a 2-state discrete Markov model. Results: Between December 2012 and June 2016, there were 755 pediatric sporadic norovirus cases and 45 reported outbreaks. Almost half (42.2%) of outbreaks occurred in long-term care facilities. Most sporadic cases (74.9%) and reported outbreaks (86.8%) occurred between November and April. Peak sporadic norovirus activity was often contemporaneous with outbreak occurrence. Among both sporadic cases and outbreaks, GII genogroup noroviruses were most prevalent (90.1% and 83.3%), with GII.4 being the dominant genotype (39.0% and 52.8%). The predictive model suggested that the 3-day moving average of sporadic cases was positively associated with the probability of an outbreak occurring. Conclusions: Despite the demographic differences between the surveillance populations, the seasonal and genotypic associations between sporadic cases and outbreaks are suggestive of contemporaneous community transmission. Public health agencies may use this knowledge to expand surveillance and identify target populations for interventions, including future vaccines. Abstract : Data from 2 demographically distinct surveillance populations were analyzed to describe norovirus epidemiology within middle Tennessee. The temporal and genotypic characteristics of sporadic norovirus in a pediatric population were reflective of those among reported outbreaks in the greater region.